If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14x + -5 + 2x + -3 = 13x + -2 + 2x Reorder the terms: -5 + -3 + 14x + 2x = 13x + -2 + 2x Combine like terms: -5 + -3 = -8 -8 + 14x + 2x = 13x + -2 + 2x Combine like terms: 14x + 2x = 16x -8 + 16x = 13x + -2 + 2x Reorder the terms: -8 + 16x = -2 + 13x + 2x Combine like terms: 13x + 2x = 15x -8 + 16x = -2 + 15x Solving -8 + 16x = -2 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. -8 + 16x + -15x = -2 + 15x + -15x Combine like terms: 16x + -15x = 1x -8 + 1x = -2 + 15x + -15x Combine like terms: 15x + -15x = 0 -8 + 1x = -2 + 0 -8 + 1x = -2 Add '8' to each side of the equation. -8 + 8 + 1x = -2 + 8 Combine like terms: -8 + 8 = 0 0 + 1x = -2 + 8 1x = -2 + 8 Combine like terms: -2 + 8 = 6 1x = 6 Divide each side by '1'. x = 6 Simplifying x = 6
| 5x-3(x-2)=-7+5x-5 | | 25+5g=115 | | 9-6x+3x=0 | | 3x+15=2* | | 4-3x-4x=-59 | | y^2+8y+64=0 | | 0.35+0.05(18-x)=0.10(15) | | 5-7x-2x=-4 | | (X+5)(-4x-2)= | | 5x+5=85 | | 14t=12 | | x+4-4x=-11 | | -6x^2+52x+90=0 | | -41=-7x-4x+3 | | -12(y+3)+4(4y-5)=3(y-6)+11 | | -1+3x-6x=-1 | | 9+11=25 | | F-32=1.8v | | 2x^2-8=5x | | X+(-X+795)y=420 | | 3-5=2+14 | | -8+x-7x=46 | | 18(y-19)=y+-57 | | 7x+3(4x-1)=-7.9 | | (2x-5)(2x+6)= | | (2x-5)(2x+6)= | | x-4+6x=-74 | | 14+x+y=36 | | 4x-x-4=25 | | 4-2x-2x=-20 | | -2(y-3)+5y=7y-4y-2 | | 3+3*2= |